2009
DOI: 10.1111/j.1442-200x.2008.02790.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic spectrum of congenital hypothyroidism in Turkish children

Abstract: To determine etiologic diagnosis, radionuclide methods and sonographic modalities should be assessed together. The gold standard in the diagnosis of ectopic thyroid tissue is thyroid scintigraphy. CDU may be a major supportive diagnostic tool in the evaluation of ectopic thyroid gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 15 publications
3
25
1
8
Order By: Relevance
“…Thyroid dysgenesis was found in 52.2% of the subjects and dyshormogenesis was found in 47.8%. Although the number of subjects with dyshormogenesis was higher than expected, it was compatible with the study of Tamam et al (6). The absence of consanguineous marriage in all patients with PCH with dyshormogenesis in our study suggests that factors other than Mendelian inheritance should be investigated in the etiology.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…Thyroid dysgenesis was found in 52.2% of the subjects and dyshormogenesis was found in 47.8%. Although the number of subjects with dyshormogenesis was higher than expected, it was compatible with the study of Tamam et al (6). The absence of consanguineous marriage in all patients with PCH with dyshormogenesis in our study suggests that factors other than Mendelian inheritance should be investigated in the etiology.…”
Section: Discussionsupporting
confidence: 79%
“…In the literature, the prevalence of transient PCH has been reported to range between 40.2% and 54% in studies related with PCH (5,6,16,18). In a study that showed the neonatal hypothyroidism screening results of 2008-2010 in our country, the prevalence of PCH was reported as 1/650, but the prevalence of permanent and transient PCH was not specified (17).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations